Disclosure of Directors' Personal Information in Hong Kong. (December 2014) - Chan, Raymond Siu Yeung; Ho, John Kong Shan
Following the lead of the UK and Australia, Hong Kong recently proposed the tightening up of access by the public to directors' residential addresses and identity card or passport numbers during its reform of the Companies Ordinance, but encountered strong opposition from the media and various professional bodies, leading to the government's decision to shelve the proposal. This paper highlights the lessons that the Hong Kong government should learn from this failure to transplant a corporate law reform, which overlooked the differences in the unique local situations.